Peningkatan Keterampilan Komputer dan Pengenalan Perangkat Lunak Microsoft Office Bagi Guru dan Siswa SD N 17 Kota Bengkulu - Khairullah; Surya Ade Saputera; Sandhy Fernandez; Sherly Yuslita; M. Medison Sanjaya; Heru franata; Basyirin Ariansyah (JURNAL ABDIMAS SERAWAI, 2021)
The development of information technology does not only play a role in the economic field, but also in the field of education. Today every teacher and school student at almost all levels of education is required to be technology literate, especially information technology because every job has been in contact with information technology. In addition to supporting educational activities, information technology literacy also supports teachers in solving administrative problems and for students to support the learning system. One of the software that can be used to support education and administrative issues is Microsoft Word, Microsoft Excel and Microsoft PowerPoint. Microsoft Word, Microsoft Excel and Microsoft PowerPoint software has many features that are still not familiar to some users, especially elementary school teachers, especially elementary school students. This is also experienced by the teachers of SD 17 Bengkulu City who are not familiar with the many tools provided in Microsoft Word, Microsoft Excel and Microsoft PowerPoint software. Some of the obstacles that are often encountered are the less than optimal use of the merge function in Word, the function of conditional formulas in Excel and animation and multimedia in PowerPoint. This is the background for the dedication team to provide training "Improving the Skills in Using Microsoft Office Software for Teachers and Students at SDN 17 Bengkulu City". This activity was held in the classroom of SD N 17 Bengkulu city with lecture methods and direct practice. The participants of this training were teachers and grade 6 students, all of whom were teachers and students of SDN 17 Bengkulu City